Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data - Yuanmeng M. Zhang; Sofia I. Sheikh; Anna K. G. Ward; Andrew A. Forbes; Kirsten M. Prior; Graham N. Stone; Michael W. Gates; Scott P. Egan; Linyi Zhang; Charles Davis; Kelly L. Weinersmith; George Melika; et al. (Molecular Ecology, 2022)
Cryptic species diversity is a major challenge regarding the species‐rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed by the parasitoid community, with reciprocal selection driving diversification of the parasitoids. Using a rare, continental‐scale data set of Sycophila parasitoid wasps reared from 44 species of cynipid galls from 18 species of oak across the USA, we combined mitochondrial DNA barcodes, ultraconserved elements (UCEs), morphological and natural history data to delimit putative species. Using these results, we generate the first large‐scale assessment of ecological specialization and host association in this species‐rich group, with implications for evolutionary ecology and biocontrol. We find most Sycophila target specific subsets of available cynipid host galls with similar morphologies, and generally attack larger galls. Our results suggest that parasitoid wasps such as Sycophila have adaptations allowing them to exploit particular host trait combinations, while hosts with contrasting traits are resistant to attack. These findings support the tritrophic niche concept for the structuring of plant–herbivore–parasitoid communities.

A tale of two tissues: Probing gene expression in a complex insect‐induced gall - Jack C. Schultz; Graham N. Stone (Molecular Ecology, 2022)
Plant galls are novel and sometimes dramatic plant organs whose development is initiated and controlled by parasitic microbes, nematodes, insects and mites. For arthropods, galls provide relative safety from enemies and abiotic stresses while providing nutrition. Galls are formed entirely by the plant, whose transcriptional pathways are modified and coopted to produce a structure specific to the galler species; they comprise a classic example of Dawkins’ “extended phenotype”. Arthropod‐elicited galls are unique in that they are often anatomically complex (Figure 1a), with multiple differentiated tissue types (Figure 1b). A growing number of investigators have studied changes in hostplant gene expression to understand arthropod gall development. In this issue of Molecular Ecology , Martinson et al. (2021) report using RNA sequencing to explore tissue‐specific gene expression associated with anatomical and functional gall complexity, demonstrating for the first time that gall tissues are as different transcriptionally as they are anatomically.

Discordant Pleistocene population size histories in a guild of hymenopteran parasitoids - William Walton; Graham N. Stone; Konrad Lohse (Molecular Ecology, 2021)
Signatures of past changes in population size have been detected in genome‐wide variation in many species. However, the causes of such demographic changes and the extent to which they are shared across co‐distributed species remain poorly understood. During Pleistocene glacial maxima, many temperate European species were confined to southern refugia. While vicariance and range expansion processes associated with glacial cycles have been widely documented, it is unclear whether refugial populations of co‐distributed species have experienced shared histories of population size change. We analyse whole‐genome sequence data to reconstruct and compare demographic histories during the Quaternary for Iberian refuge populations in a single ecological guild (seven species of chalcid parasitoid wasps associated with oak cynipid galls). For four of these species, we find support for large changes in effective population size ( N e ) through the Pleistocene that coincide with major climate events. However, there is little evidence that the timing, direction and magnitude of demographic change are shared across species, suggesting that demographic histories in this guild are largely idiosyncratic, even at the scale of a single glacial refugium.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Low‐coverage genomic data resolve the population divergence and gene flow history of an Australian rain forest fig wasp - Lisa Cooper; Lynsey Bunnefeld; Jack Hearn; James M. Cook; Konrad Lohse; Graham N. Stone (Molecular Ecology, 2020)
Population divergence and gene flow are key processes in evolution and ecology. Model‐based analysis of genome‐wide data sets allows discrimination between alternative scenarios for these processes even in nonmodel taxa. We used two complementary approaches (one based on the blockwise site frequency spectrum [bSFS], the second on the pairwise sequentially Markovian coalescent [PSMC]) to infer the divergence history of a fig wasp, Pleistodontes nigriventris . Pleistodontes nigriventris and its fig tree mutualist Ficus watkinsiana are restricted to rain forest patches along the eastern coast of Australia and are separated into The Northern population is to the north of the Southern populations by two dry forest corridors (the Burdekin and St. Lawrence Gaps). We generated whole genome sequence data for two haploid males per population and used the bSFS approach to infer the timing of divergence between northern and southern populations of P. nigriventris , and to discriminate between alternative isolation with migration (IM) and instantaneous admixture (ADM) models of postdivergence gene flow. Pleistodontes nigriventris has low genetic diversity (π = 0.0008), to our knowledge one of the lowest estimates reported for a sexually reproducing arthropod. We find strongest support for an ADM model in which the two populations diverged ca . 196 kya in the late Pleistocene, with almost 25% of northern lineages introduced from the south during an admixture event ca. 57 kya. This divergence history is highly concordant with individual population demographies inferred from each pair of haploid males using PSMC. Our analysis illustrates the inferences possible with genome‐level data for small population samples of tiny, nonmodel organisms and adds to a growing body of knowledge on the population structure of Australian rain forest taxa.

Gradients in richness and turnover of a forest passerine's diet prior to breeding: A mixed model approach applied to faecal metabarcoding data - Jack D. Shutt; James A. Nicholls; Urmi H. Trivedi; Malcolm D. Burgess; Graham N. Stone; Jarrod D. Hadfield; Albert B. Phillimore (Molecular Ecology, 2020)
Rather little is known about the dietary richness and variation of generalist insectivorous species, including birds, due primarily to difficulties in prey identification. Using faecal metabarcoding, we provide the most comprehensive analysis of a passerine's diet to date, identifying the relative magnitudes of biogeographic, habitat and temporal trends in the richness and turnover in diet of Cyanistes caeruleus (blue tit) along a 39 site and 2° latitudinal transect in Scotland. Faecal samples were collected in 2014–2015 from adult birds roosting in nestboxes prior to nest building. DNA was extracted from 793 samples and we amplified COI and 16S minibarcodes. We identified 432 molecular operational taxonomic units that correspond to putative dietary items. Most dietary items were rare, with Lepidoptera being the most abundant and taxon‐rich prey order. Here, we present a statistical approach for estimation of gradients and intersample variation in taxonomic richness and turnover using a generalised linear mixed model. We discuss the merits of this approach over existing tools and present methods for model‐based estimation of repeatability, taxon richness and Jaccard indices. We found that dietary richness increases significantly as spring advances, but changes little with elevation, latitude or local tree composition. In comparison, dietary composition exhibits significant turnover along temporal and spatial gradients and among sites. Our study shows the promise of faecal metabarcoding for inferring the macroecology of food webs, but we also highlight the challenge posed by contamination and make recommendations of laboratory and statistical practices to minimise its impact on inference.

Introduction: Special issue on species interactions, ecological networks and community dynamics – Untangling the entangled bank using molecular techniques - Tomas Roslin; Michael Traugott; Mattias Jonsson; Graham N. Stone; Simon Creer; William O. C. Symondson (Molecular Ecology, 2019)

Tournament ABC analysis of the western Palaearctic population history of an oak gall wasp, Synergus umbraculus - Graham N. Stone; Sarah C. White; György Csóka; George Melika; Serap Mutun; Zsolt Pénzes; S. Ebrahim Sadeghi; Karsten Schönrogge; Majid Tavakoli; James A. Nicholls (Molecular Ecology, 2017)
Approximate Bayesian computation ( ABC ) is a powerful and widely used approach in inference of population history. However, the computational effort required to discriminate among alternative historical scenarios often limits the set that is compared to those considered more likely a priori. While often justifiable, this approach will fail to consider unexpected but well‐supported population histories. We used a hierarchical tournament approach, in which subsets of scenarios are compared in a first round of ABC analyses and the winners are compared in a second analysis, to reconstruct the population history of an oak gall wasp, Synergus umbraculus (Hymenoptera, Cynipidae) across the Western Palaearctic. We used 4,233 bp of sequence data across seven loci to explore the relationships between four putative Pleistocene refuge populations in Iberia, Italy, the Balkans and Western Asia. We compared support for 148 alternative scenarios in eight pools, each pool comprising all possible rearrangements of four populations over a given topology of relationships, with or without founding of one population by admixture and with or without an unsampled “ghost” population. We found very little support for the directional “out of the east” scenario previously inferred for other gall wasp community members. Instead, the best‐supported models identified Iberia as the first‐regional population to diverge from the others in the late Pleistocene, followed by divergence between the Balkans and Western Asia, and founding of the Italian population through late Pleistocene admixture from Iberia and the Balkans. We compare these results with what is known for other members of the oak gall community, and consider the strengths and weaknesses of using a tournament approach to explore phylogeographic model space.

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

ABC inference of multi‐population divergence with admixture from unphased population genomic data - John D. Robinson; Lynsey Bunnefeld; Jack Hearn; Graham N. Stone; Michael J. Hickerson (Molecular Ecology, 2014)
Rapidly developing sequencing technologies and declining costs have made it possible to collect genome‐scale data from population‐level samples in nonmodel systems. Inferential tools for historical demography given these data sets are, at present, underdeveloped. In particular, approximate Bayesian computation ( ABC ) has yet to be widely embraced by researchers generating these data. Here, we demonstrate the promise of ABC for analysis of the large data sets that are now attainable from nonmodel taxa through current genomic sequencing technologies. We develop and test an ABC framework for model selection and parameter estimation, given histories of three‐population divergence with admixture. We then explore different sampling regimes to illustrate how sampling more loci, longer loci or more individuals affects the quality of model selection and parameter estimation in this ABC framework. Our results show that inferences improved substantially with increases in the number and/or length of sequenced loci, while less benefit was gained by sampling large numbers of individuals. Optimal sampling strategies given our inferential models included at least 2000 loci, each approximately 2 kb in length, sampled from five diploid individuals per population, although specific strategies are model and question dependent. We tested our ABC approach through simulation‐based cross‐validations and illustrate its application using previously analysed data from the oak gall wasp, Biorhiza pallida .

Likelihood‐based inference of population history from low‐coverage de novo genome assemblies - Jack Hearn; Graham N. Stone; Lynsey Bunnefeld; James A. Nicholls; Nicholas H. Barton; Konrad Lohse (Molecular Ecology, 2014)
Short‐read sequencing technologies have in principle made it feasible to draw detailed inferences about the recent history of any organism. In practice, however, this remains challenging due to the difficulty of genome assembly in most organisms and the lack of statistical methods powerful enough to discriminate between recent, nonequilibrium histories. We address both the assembly and inference challenges. We develop a bioinformatic pipeline for generating outgroup‐rooted alignments of orthologous sequence blocks from de novo low‐coverage short‐read data for a small number of genomes, and show how such sequence blocks can be used to fit explicit models of population divergence and admixture in a likelihood framework. To illustrate our approach, we reconstruct the Pleistocene history of an oak‐feeding insect (the oak gallwasp Biorhiza pallida ), which, in common with many other taxa, was restricted during Pleistocene ice ages to a longitudinal series of southern refugia spanning the Western Palaearctic. Our analysis of sequence blocks sampled from a single genome from each of three major glacial refugia reveals support for an unexpected history dominated by recent admixture. Despite the fact that 80% of the genome is affected by admixture during the last glacial cycle, we are able to infer the deeper divergence history of these populations. These inferences are robust to variation in block length, mutation model and the sampling location of individual genomes within refugia. This combination of de novo assembly and numerical likelihood calculation provides a powerful framework for estimating recent population history that can be applied to any organism without the need for prior genetic resources.

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

A likelihood‐based comparison of population histories in a parasitoid guild - Konrad Lohse; Nicholas H. Barton; George Melika; Graham N. Stone (Molecular Ecology, 2012)
Little is known about the stability of trophic relationships in complex natural communities over evolutionary timescales. Here, we use sequence data from 18 nuclear loci to reconstruct and compare the intraspecific histories of major Pleistocene refugial populations in the Middle East, the Balkans and Iberia in a guild of four Chalcid parasitoids ( Cecidostiba fungosa , Cecidostiba semifascia , Hobbya stenonota and Mesopolobus amaenus ) all attacking Cynipid oak galls. We develop a likelihood method to numerically estimate models of divergence between three populations from multilocus data. We investigate the power of this framework on simulated data, and—using triplet alignments of intronic loci—quantify the support for all possible divergence relationships between refugial populations in the four parasitoids. Although an East to West order of population divergence has highest support in all but one species, we cannot rule out alternative population tree topologies. Comparing the estimated times of population splits between species, we find that one species, M. amaenus , has a significantly older history than the rest of the guild and must have arrived in central Europe at least one glacial cycle prior to other guild members. This suggests that although all four species may share a common origin in the East, they expanded westwards into Europe at different times.

Mitochondrial barcodes are diagnostic of shared refugia but not species in hybridizing oak gallwasps - JAMES A. NICHOLLS; RICHARD J. CHALLIS; SERAP MUTUN; GRAHAM N. STONE (Molecular Ecology, 2012)
Mitochondrial DNA barcodes provide a simple taxonomic tool for systematic and ecological research, with particular benefit for poorly studied or species‐rich taxa. Barcoding assumes genetic diversity follows species boundaries; however, many processes disrupt species‐level monophyly of barcodes leading to incorrect classifications. Spatial population structure, particularly when shared across closely related and potentially hybridizing taxa, can invalidate barcoding approaches yet few data exist to examine its impacts. We test how shared population structure across hybridizing species impacts upon mitochondrial barcodes by sequencing the cytochrome b gene for 518 individuals of four well‐delimited Western Palaearctic gallwasp species within the Andricus quercuscalicis species group. Mitochondrial barcodes clustered individuals into mixed‐species clades corresponding to refugia, with no difference in within‐ and between‐species divergence. Four nuclear genes were also sequenced from 4 to 11 individuals per refugial population of each species. Multi‐locus analyses of these data supported established species, with no support for the refugial clustering across species seen in mitochondrial barcodes. This pattern is consistent with mitochondrial introgression among populations of species sharing the same glacial refugium, such that mitochondrial barcodes identify a shared history of population structure rather than species. Many taxa show phylogeographic structure across glacial refugia, suggesting that mitochondrial barcoding may fail when applied to other sets of co‐distributed, closely related species. Robust barcoding approaches must sample extensively across population structure to disentangle spatial from species‐level variation. Methods incorporating multiple unlinked loci are also essential to accommodate coalescent variation among genes and provide power to resolve recently diverged species.

Torymus sinensis: a viable management option for the biological control of Dryocosmus kuriphilus in Europe? - Melanie Gibbs; Karsten Schönrogge; Alberto Alma; George Melika; Ambra Quacchia; Graham N. Stone; Alexandre Aebi (BioControl, 2011)

Concordant phylogeography and cryptic speciation in two Western Palaearctic oak gall parasitoid species complexes - JAMES A. NICHOLLS; SONJA PREUSS; ALEXANDER HAYWARD; GEORGE MELIKA; GYÖRGY CSÓKA; JOSÉ-LUIS NIEVES-ALDREY; RICHARD R. ASKEW; MAJID TAVAKOLI; KARSTEN SCHÖNROGGE; GRAHAM N. STONE (Molecular Ecology, 2010)

Plant remains from the Kreftenheye Formation (Eemian) at Raalte, The Netherlands - Raymond W. J. M. van der Ham; Wim J. Kuijper; M. Joop H. Kortselius; Johan van der Burgh; Graham N. Stone; Jan G. Brewer (Vegetation History and Archaeobotany, 2008)

Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps - GRAHAM N. STONE; RACHEL J. ATKINSON; ANTONIS ROKAS; JOSÉ‐LUIS NIEVES ALDREY; GEORGE MELIKA; ZOLTAN Ács; GYÖRGY CSÓKA; ALEXANDER HAYWARD; RICHARD BAILEY; CAROLINE BUCKEE; GILEAN A. T. McVEAN (Molecular Ecology, 2008)
Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the possibility of widespread secondary loss of sex in the Cynipini, and of diversification within purely parthenogenetic lineages. We use two approaches based on analyses of allele frequency data to test for cryptic sexual generations in eight apparently asexual European species distributed through a major western palaearctic lineage of the gallwasp genus Andricus . All species showing adequate levels of polymorphism (7/8) showed signatures of sex compatible with cyclical parthenogenesis. We also use DNA sequence data to test the hypothesis that ignorance of these sexual generations (despite extensive study on this group) results from failure to discriminate among known but morphologically indistinguishable sexual generations. This hypothesis is supported: 35 sequences attributed by leading cynipid taxonomists to a single sexual adult morphospecies, Andricus burgundus, were found to represent the sexual generations of at least six Andricus species. We confirm cryptic sexual generations in a total of 11 Andricus species, suggesting that secondary loss of sex is rare in Andricus .

Plant–pollinator interactions in a Mexican Acacia community - Nigel E. Raine; Alice Sharp Pierson; Graham N. Stone (Arthropod-Plant Interactions, 2007)

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.

Longitudinal range expansion and cryptic eastern species in the western Palaearctic oak gallwasp, Andricus coriarius - RICHARD J. CHALLIS; SERAP MUTUN; JOSE‐LUIS NIEVES‐ALDREY; SONJA PREUSS; ANTONIS ROKAS; ALEXANDRE AEBI; EBRAHIM SADEGHI; MAJID TAVAKOLI; GRAHAM N. STONE (Molecular Ecology, 2007)
The oak gallwasp Andricus coriarius is distributed across the Western Palaearctic from Morocco to Iran. It belongs to a clade of host‐alternating Andricus species that requires host oaks in two sections of Quercus subgenus Quercus to complete its lifecycle, a requirement that has restricted the historic distribution and dispersal of members of this clade. Here we present nuclear and mitochondrial sequence evidence from the entire geographic range of A. coriarius to investigate the genetic legacy of longitudinal range expansion. We show A. coriarius as currently understood to be para‐ or polyphyletic, with three evolutionarily independent (but partially sympatric) lineages that diverged c. 10 million years ago (mya). The similarities in gall structure that have justified recognition of single species to date thus represent either strong conservation of an ancestral state or striking convergence. All three lineages originated in areas to the east of Europe, underlining the significance of Turkey, Iran and the Levant as ‘cradles’ of gallwasp evolution. One of the three lineages gave rise to all European populations, and range expansion from a putative Eastern origin to the present distribution is predicted to have occurred around 1.6 mya.

Comparative phylogeography across two trophic levels: the oak gall wasp Andricus kollari and its chalcid parasitoid Megastigmus stigmatizans - ALEXANDER HAYWARD; GRAHAM N. STONE (Molecular Ecology, 2006)
Insect parasitoids are important components of many terrestrial ecosystems. However, relatively little is known about the mechanisms responsible for structuring their populations. Here we investigate the ability of Megastigmus stigmatizans , an oak gall wasp parasitoid, to track its host Andricus kollari over two different timescales, and examine its current population structure across a divide in host population structure. The divide represents a transition in gall wasp host‐plant species and offers the opportunity to examine whether the split, which divides gall wasp populations, manifests itself in the next trophic level. Analysis of mitochondrial haplotype data for parasitoid and host reveals: (i) A similar phylogeographic population structure for both, with Iberian populations more derived with respect to more eastern populations. (ii) It is likely that the host colonized the Iberian refuge earlier than the parasitoid, probably by at least one glacial cycle. (iii) Recent range expansion of central European host populations northwards has resulted in pursuit by parasitoids from the same geographic origin. (iv) In addition, Iberian parasitoid populations have crossed a major divide in host population structure to invade northern Europe. Such human‐facilitated escape from natural refugial distributions may have important implications for the composition and structure of northern European gall wasp communities.

Out of Anatolia: longitudinal gradients in genetic diversity support an eastern origin for a circum‐Mediterranean oak gallwasp Andricus quercustozae - Antonis Rokas; Rachel J. Atkinson; Lucy Webster; György Csóka; Graham N. Stone (Molecular Ecology, 2003)
Many studies have addressed the latitudinal gradients in intraspecific genetic diversity of European taxa generated during postglacial range expansion from southern refugia. Although Asia Minor is known to be a centre of diversity for many taxa, relatively few studies have considered its potential role as a Pleistocene refugium or a potential source for more ancient westward range expansion into Europe. Here we address these issues for an oak gallwasp, Andricus quercustozae (Hymenoptera: Cynipidae), whose distribution extends from Morocco along the northern coast of the Mediterranean through Turkey to Iran. We use sequence data for a fragment of the mitochondrial gene cytochrome b and allele frequency data for 12 polymorphic allozyme loci to answer the following questions: (1) which regions represent current centres of genetic diversity for A. quercustozae ? Do eastern populations represent one refuge or several discrete glacial refugia? (2) Can we infer the timescale and sequence of the colonization processes linking current centres of diversity? Our results suggest that A. quercustozae was present in five distinct refugia (Iberia, Italy, the Balkans, southwestern Turkey and northeastern Turkey) with recent genetic exchange between Italy and Hungary. Genetic diversity is greatest in the Turkish refugia, suggesting that European populations are either (a) derived from Asia Minor, or (b) subject to more frequent population bottlenecks. Although Iberian populations show the lowest diversity for putatively selectively neutral markers, they have colonized a new oak host and represent a genetically and biologically discrete entity within the species.

Scanning for telomeric deletions and duplications and uniparental disomy using genetic markers in 120 children with malformations - M. Rosenberg; C. Killoran; L. Dziadzio; S. Chang; D. Stone; J. Meck; D. Aughton; L. Bird; J. Bodurtha; S. Cassidy; J. Graham; A. Grix; et al. (Human Genetics, 2001)

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari : a tale of two lifecycles - Graham Stone; Rachel Atkinson; Antonis Rokas; György Csóka; José‐Luis Nieves‐Aldrey (Molecular Ecology, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris , while in Iberia and North Africa the sexual generation host is cork oak, Q. suber . Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cerris from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari ? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south‐west France are allied to Spain, while all remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south‐west France is marked by abrupt transitions in the frequency of refuge‐specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north‐west France, none were detected where the two lifecycles meet in south‐western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow, and limited to regions where Q. cerris and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.